Preschool children's toothbrushing behaviour and association with their oral health / Iqra Muhammad Khan - Iqra , Muhammad Khan (2020)
Toothbrushing is an important yet neglected behaviour that has affected oral health of preschool children (4-6 years). Factors like dietary habit, socioeconomic status and oral conditions also affect oral health of preschool children. Despite intervention efforts, recent investigations reported high prevalence of early childhood caries (ECC) and oral diseases among this age group across different populations. Therefore, it is imperative to understand the relationship between toothbrushing behaviour and oral health status of preschool children to prevent oral diseases, hence improve their oral health. The aim of the current study was to evaluate toothbrushing behaviour of preschool children, assess their oral health status and determine their association. It was a single visit cross-sectional study. A written informed consent was obtained from the parents/guardians of 92 eligible participants. Preschool children’s toothbrushing behaviour was evaluated from parental responses (questionnaire) followed by observation (video recording) of their toothbrushing. The extent of parents/guardians’ involvement in their children’s toothbrushing was also observed and scored according to the formulated criteria. The oral health status was assessed in terms of pre and post brushing plaque scores (used Mira-2- tone for plaque identification), gingival index and dental caries status. The data from assessment of toothbrushing behaviour and oral health status was analyzed using SPSS. A novel ‘Behavioural Observation Research Interactive Software’ (BORIS) was used to v analyse toothbrushing videos. Another advanced Smart PLS 3 software was used to perform a second-generation multivariate analysis to create models that depicted the association between children’s toothbrushing behaviour and oral health status with and without confounding variables. The impact of other factors was also analyzed as confounders. About two-third of participants were of Malay ethnicity. Slightly more than half (53%) were girls and 38% were 4years old. Majority (90%) of parents/guardians had tertiary level education. The descriptive statistics revealed that there was a difference in the recorded values of both methods (quantitative and qualitative) of toothbrushing behaviour. About 35% of parents reported that their children used pea sized toothpaste but only 28% were observed. Fifty one percent were observed to brush for 1-2mins, however the reported data suggested only 40% to brush for 30sec-1min. A difference of 30% was recorded between reported (80%) and observed fluoride toothpaste (F lesser than 1000ppm) use. Almost 30% were observed to use fluoridated toothpaste (F greater than 1000ppm) and 20% non-fluoridated toothpaste. Slightly more than half of parents/guardians reported to guide their children occasionally but only 11% were observed to supervise them. The mean plaque score reduction after observed toothbrushing was 10.80 (2.46), mean pre-brushing plaque score was 90.3 (10.2), mean gingival index was 0.89 (0.65) and mean dental caries status dfs (1-6) was 18.87 (12.39).Toothbrushing behaviour contributed to plaque score change (86%), dental caries status(73%), gingival index (66%) and pre-brushing plaque score (31%). The significant confounding variables had a small influence on oral health of preschool children. vi Preschool children had inadequate toothbrushing behaviour and poor oral health status with a statically significant association between them. Keywords: Early childhood caries (ECC), oral health, plaque score, preschool children, toothbrushing behaviour.